Implementation Of Traditional Congklak Game-Based Learning To Improve The Numeracy Of Grade 3 Students Of SDN 3 Menggala In The 2024/2025 Academic Year - M. Baehaki; Sukarto Sukarto; Musafir Musafir (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This classroom action research aims to enhance the numeracy skills of 3rd-grade students at SDN 3 Menggala through the traditional Congklak game. Data collection techniques included observation, interviews, tests, and documentation, with observation guides, interview guides, test guides, and documentation guides as data collection tools. The results showed a significant increase in students' numeracy skills, from an initial 23% to 46.1% in the first cycle, and further to 84.6% in the second cycle. This demonstrates that the Congklak game is effective in improving numeracy. The average numeracy ability of students increased according to predetermined success criteria, proving the effectiveness of this approach.